Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Debre Berhan University - International Livestock Research Institute; Debre Berhan University (2021)
Memorandum of understanding (MOU) between the International Livestock Research Institute (ILRI) and Debre BerhanUniversity. MOU signed on December 23, 2021, by Jimmy Smith, Director-General of ILRI and Nigus Tadesse, President of Debre Berhan University.